Implementation of Transmitter Zigbee System based on Wireless Sensor Network of IEEE 802.15.4 Standard - Hamza, Ekhlas K.; Hadi, Russul H. (Al-Khwarizmi Engineering Journal, 2017)
Abstract Zigbee is considered to be one of the wireless sensor networks (WSNs) designed for short-range communications applications. It follows IEEE 802.15.4 specifications that aim to design networks with lowest cost and power consuming in addition to the minimum possible data rate. In this paper, a transmitter Zigbee system is designed based on PHY layer specifications of this standard. The modulation technique applied in this design is the offset quadrature phase shift keying (OQPSK) with half sine pulse-shaping for achieving a minimum possible amount of phase transitions. In addition, the applied spreading technique is direct sequence spread spectrum (DSSS) technique, which has the effect in getting better performance for the transmitter system in multipath environments. The system is developed through the use of MATLAB/Simulink to show the performance of the proposed system in response to the appliy modulation technique. Keywords: DSSS technique, IEEE 802.15.4, MSK, OQPSK, Zigbee.